Desire satisfaction and its discontents - Farokhi Kakesh, Hadis (THEORIA. An International Journal for Theory, History and Foundations of Science, 2023)
According to a well-established view of desire satisfaction, a desire that p is satisfied iff p obtains. Call this the 'standard view'. The standard view is purely semantic, which means the satisfaction condition of desires is placed in the truth of the embedded proposition that indicates the content of the desire. This paper aims to defend the standard view against two frequently discussed problems: the problem of underspecification and desires conditional on their own persistence. The former holds that the standard view cannot capture the specific ways of desire satisfaction. The latter holds that the standard view does not provide sufficient conditions for the satisfaction of desires conditional on their own persistence. To address the first problem, I will disambiguate different interpretations of desire ascriptions using de re/de dicto distinction. My argument to address the second problem rests on the disambiguation of different senses of satisfaction: semantic and agent.